PENGARUH PEMBELAJARAN ETHNOMATEMATIKA TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH DASAR - Nurjanah, Siti; Fadhilaturrahmi; Marta, Rusdial; Nurhaswinda; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of mathematics learning in developing students' critical thinking skills, focusing on the ethnomathematics approach. At SDN 007 Bangkinang and SDN 013 Tanjung Berulak, it was found that students tended to provide short and less in-depth answers in solving mathematical problems, indicating low critical thinking skills among the students. The method used was quasi-experimental, involving 40 fourth-grade students, 20 students from SDN 007 Bangkinang as the experimental class and, 20 students from SDN 013 Tanjung Berulak as the control class. The research instrument consisted of story problems with five questions, each containing four indicators of critical thinking skills. Data were analyzed using an independent samples t-test. The results showed that ethnomathematics learning had a significant effect on improving students' critical thinking skills, with a mean difference of -34.075 and a significance level of 0.000 (p < 0.05). The average score of students' critical thinking skills increased to 78.00. These findings support the importance of integrating culture into mathematics learning to effectively enhance students' critical thinking abilities.